Physical Activity and Blood Lipids and Lipoproteins in Dialysis Patients - Hiroyuki Imamura; Keiko Mizuuchi; Reika Oshikata (International Journal of Nephrology)
The relationship between physical activity and blood lipids and lipoproteins in dialysis patients is reviewed in the context of the potentially confounding factors such as nutritional intake, cigarette smoking, obesity, alcohol intake, and physical activity levels in the general population and additional confounding factors such as mode of dialysis and diabetes in dialysis patients. The known associations in the general population of physical activity with high-density-lipoprotein cholesterol subfractions and apolipoprotein A-I are more pronounced in hemodialysis patients than in peritoneal dialysis patients even after adjusting for these confounding factors. Examining studies on the effects of physical activity on blood lipids and lipoproteins, the most consistent observation is the noted decrease in triglycerides and increase in high-density-lipoprotein cholesterol and insulin sensitivity in hemodialysis patients. The changes in lipids and lipoproteins in hemodialysis patients could be caused by changes in activity levels of lipoprotein lipase, insulin sensitivity, and/or glucose metabolism. Future research investigating the relationship between physical activity and blood lipids and lipoproteins in dialysis patients should direct research towards the underlying mechanisms for changes in blood lipids and lipoproteins.